1987
DOI: 10.3171/jns.1987.66.6.0875
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of catecholamines in assessing outcome in traumatic brain injury

Abstract: Because of the central role of the sympathetic nervous system in mediating the stress response, plasma norepinephrine (NE), epinephrine (E), and dopamine (DA) levels were measured in 61 traumatically brain-injured patients to determine whether catecholamine (CA) levels obtained within 48 hours after injury provide reliable prognostic markers of outcome. Patient outcome was determined at 1 week using the Glasgow Coma Scale (GCS) and at the time of discharge using the Glasgow Outcome Scale (GOS). Levels of NE, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(90 citation statements)
references
References 28 publications
1
87
2
Order By: Relevance
“…It is suggested that these findings support the mechanism of catecholamine-mediated myocardial injury. A previous study indicated that serum levels of catecholamines also correlate with the severity of traumatic brain injury [41]. In our study, increased plasma levels of NE and 24-hour urine NE were not correlated with the severity of SAH.…”
Section: Discussioncontrasting
confidence: 30%
“…It is suggested that these findings support the mechanism of catecholamine-mediated myocardial injury. A previous study indicated that serum levels of catecholamines also correlate with the severity of traumatic brain injury [41]. In our study, increased plasma levels of NE and 24-hour urine NE were not correlated with the severity of SAH.…”
Section: Discussioncontrasting
confidence: 30%
“…23,24 Previous studies indicate that serum levels of catecholamines correlate with the severity of neurological injury and neurological outcome. 18 However, animal models indicate that the direct release of toxic levels of catecholamines into the myocardium by the cardiac sympathetic nerve terminals is a more likely cause of neurocardiogenic injury than is adrenal release of catecholamines into the systemic circulation. 25 Higher HuntHess grades indicate greater neurological injury and thus may be associated with a greater degree of sympathetic outflow to the heart.…”
Section: Discussionmentioning
confidence: 99%
“…1 Survivors of TBI often experience profound catecholamine surges and additional systemic complications such as hypertension, pulmonary edema, and cardiomyopathy. [2][3][4][5][6][7][8][9] Notably, endothelial dysfunction secondary to systemic inflammation and shock is widely believed to contribute to systemic complications in severe trauma, 9,10 yet there have been no studies that directly measure endothelial function in systemic blood vessels after head trauma.…”
Section: Introductionmentioning
confidence: 99%